1999
DOI: 10.1002/cjce.5450770311
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of uranium and 226ra from low‐level radioactive waste from port hope, ontario

Abstract: Uranium and radium were leached from a low-level radioactive soil sample neutralized with limestone from Port Hope, ON, in single stage and multistage leaching tests. The leachants used were alkaline EDTA, sodium citrate, sodium potassium tartrate, acidic ferric chloride, hydrochloric acid, nitric acid and hydrochloric or nitric acid plus boric acid mixtures, All leaching tests except the two-stage acid leachings proved ineffective in yielding leach residues with low residual 226Ra concentrations of < 100 pCi/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…According to the USEPA [47], natural attenuation is the "use of natural processes to contain the spread of the contamination from chemical spills and reduce the concentration and amount of pollutants at contaminated sites". It can also be termed as intrinsic remediation, bio-attenuation and intrinsic bioremediation [164,165,166]. Natural attenuation is considered to be the least invasive approach to environmental remediation.…”
Section: Natural Attenuationmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the USEPA [47], natural attenuation is the "use of natural processes to contain the spread of the contamination from chemical spills and reduce the concentration and amount of pollutants at contaminated sites". It can also be termed as intrinsic remediation, bio-attenuation and intrinsic bioremediation [164,165,166]. Natural attenuation is considered to be the least invasive approach to environmental remediation.…”
Section: Natural Attenuationmentioning
confidence: 99%
“…Several investigations on the removal of uranium from artificially contaminated soils as well as from anthropogenic sources, such as mine tailings and DU processing facilities, revealed that the application of any remedial technology for soils contaminated with uranium must take into account the potential of exposure to workers (as a consequence of the presence of radionuclides and the type and energy of radiation emitted) and the need to keep the exposure as low as reasonable achievable [147,[162][163][164]. The ultimate goal is to develop technologies that can further reduce risks, reduce cleanup costs and reduce the volume of remaining contaminated soil [15].…”
Section: In Situmentioning
confidence: 99%
“…As the pH increases, the tendency is for uranium hydroxide complexes to dominate under oxidizing conditions (positive Eh). No U(IV) cations are pre- After analysis of the Eh-pH diagram for a U system, it appears that the experimental conditions under which Nirdosh [8] performed extractions were optimal for the UO 2 2+ cation to exist. The low pH and high Eh conditions prevented the formation of solid compounds such as uraninite and schoepite.…”
Section: Introductionmentioning
confidence: 99%
“…Another method of DU extraction was reported by Nirdosh [8]. A two-stage acid leaching procedure was developed for treatment of radioactive soil waste.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation